A new perspective on the pleiotropic blood pressure improvement effect of sitagliptin: downregulation of miRNA-155 and miRNA-21 - Yilmaz-Bozoglan, M.; Gul-Kahraman, K.; Serhatlioglu, I; Onalan, E.; Akkopru, M. C.; Sahna, E. (Springernature, 2021)
INTRODUCTION: Deterioration of vascular responses is the crucial event in the initiation of cardiovascular problems in hypertension (HT) and diabetes mellitus (DM). A well-known oral antidiabetic, sitagliptin, has pleiotropic effects besides improving glycemic state in type-2 DM. This study aimed to investigate the therapeutic effect of sitagliptin on blood pressure with previously unassessed parameters of well-known pathophysiological processes and especially at the microRNA (miRNA) level where there are many unknowns. METHODS: N-nitro-L-arginine methyl ester (L-NAME)-induced HT model was performed on nondiabetic male rats. Four groups (including 7 rats in each) were formed: normotensives, sitagliptin-treated, HT and sitagliptintreated HT. Asymmetric dimethylarginine (ADMA), intercellular adhesion molecule-1 (ICAM-1) and tyrosine hydroxylase (TH), HT related miRNAs were evaluated. In-vitro vessel responses were observed. RESULTS: L-NAME led to a signifi cant increase in blood pressure. Hypertensives exhibited signifi cantly increased contractile responses, consistent with increased ADMA, ICAM-1. Sitagliptin decreased TH levels but not statistically signifi cantly. The new side of the study was the miRNA-21 and miRNA-155 expressions were in line with other parameters in both the HT and sitagliptin-treated HT groups. CONCLUSION: Sitagliptin may control comorbidities, especially HT and introduces new targets to alleviate vascular responses. The new knowledge is; sitagliptin may show these effects through microRNAs (Tab. 2, Fig. 6, Ref. 46). Text in PDF www.elis.sk
Keywords: KEY WORDS; endothelial dysfunction; infl ammation; miRNA-21; miRNA-155; sitagliptin; blood pressure